2013
DOI: 10.14202/vetworld.2013.870-873
|View full text |Cite
|
Sign up to set email alerts
|

Hemato-biochemical and therapeutic studies on Escherichia coli associated with concurrent enteric infection in lambs

Abstract: Aim: The trials were designed on 30 lambs of age below 2 weeks exhibiting the symptoms of colibacillosis. Materials and Methods:Isolation of organism and identification of pathogenic Escherichia coli was confirmed by standard cultural, microbiological, serological, and biochemical tests. Venous blood was collected aseptically for hematological studies.Result: Bacteriological examinations of fecal sample were positive for E.coli and isolates identified on the basis of morphological, cultural, and biochemical ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
1
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 7 publications
5
1
0
Order By: Relevance
“…Increase in Hb, PCV and TEC is due to dehydration and hemoconcentration which occur invariably in cases of diarrhea as fluid volume is lost from body so relative count increases. Absolute leucocytic count in diarrhoeic sheep revealed significant leucocytosis due to neutrophilia, lymphocytosis, monocytosis and eosinophilia were in unison with the previous observation of Hassen et al (2013) [5] ; Ahmed (2020) [2] and Tarunpreet et al (2019) [13] . Increased TLC might be due to reaction of body defence mechanism against infection and also due to dehydration and hemoconcentration as reported by Hassen et al (2013) [5] .…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Increase in Hb, PCV and TEC is due to dehydration and hemoconcentration which occur invariably in cases of diarrhea as fluid volume is lost from body so relative count increases. Absolute leucocytic count in diarrhoeic sheep revealed significant leucocytosis due to neutrophilia, lymphocytosis, monocytosis and eosinophilia were in unison with the previous observation of Hassen et al (2013) [5] ; Ahmed (2020) [2] and Tarunpreet et al (2019) [13] . Increased TLC might be due to reaction of body defence mechanism against infection and also due to dehydration and hemoconcentration as reported by Hassen et al (2013) [5] .…”
Section: Discussionsupporting
confidence: 87%
“…Absolute leucocytic count in diarrhoeic sheep revealed significant leucocytosis due to neutrophilia, lymphocytosis, monocytosis and eosinophilia were in unison with the previous observation of Hassen et al (2013) [5] ; Ahmed (2020) [2] and Tarunpreet et al (2019) [13] . Increased TLC might be due to reaction of body defence mechanism against infection and also due to dehydration and hemoconcentration as reported by Hassen et al (2013) [5] . Serum biochemical profiles of diarrhoeic sheep/lambs in present study were significant decrease in values of total protein, serum globulin and serum albumin where as significant increase in the albumin: globulin ratio.…”
Section: Discussionsupporting
confidence: 87%
“…The reduction of TLC indicates effective antibacterial therapy. Similar findings were also recorded in other antimicrobial therapies in E. coli diarrhea in lamb (Hassan et al 2013). The reduction of fecal consistency score and dehydration (%) in post treatment period in diarrheic calves either by ST or by ST-CoQ10 indicated clinical recovery of animal from diarrhea.…”
Section: Resultssupporting
confidence: 82%
“…In the present study, the TLC in all the weeks of transition period and control did not differ significantly in between summer and winter. In support to the present findings Aengwanich et al (2011) in cattle and Hassan et al (2013) in goats also reported the same. The lack of significant difference between the seasons under study might be attributed to the adaptation of the species to the increasing THI during summer season (Hassan et al 2013).…”
Section: Haematological Parameterssupporting
confidence: 92%